Gravidez na adolescência em Uberlândia MG: condicionantes e consequências - Vieira, Andréa dos Santos (2013)
The decline in fertility in the early 1970s provides visibility and status of health problem teenage pregnancy. The rights of sexual and reproductive health are concepts developed in recent decades and represents a historic achievement, the result of the struggle for citizenship. Teenage pregnancy and unwanted pregnancy leads to higher risk maternal-infant and social. In Uberlândia, teenage pregnancy, as well as on the national scene, has been evidenced pregnancies occurred in the county in the years 2008-2010, 15% are teenagers. Despite the decline in fertility even in the age of the teenager, the son of the teenager still had a higher risk of death in the first year of life. Having as assumptions that adolescence is a socio-historical and therefore plural and socially determined, in this context aim of the study was to analyze the social and health indicators of the female population in Uberlândia vulnerability perspective, with emphasis on territorial of intra-urban disparities in teenage pregnancy and potential coping actions, programs and projects undertaken by the state. The vulnerability is understood here as an indicator of inequality and social inequality. The type of study was descriptive case study and exploratory nature of quantitative and qualitative. The analytical techniques and statistical analyzes were spatial analysis. The geoprocessing health indicators proved to be an important tool for planning, monitoring and evaluating the performance of the network to protect teens and twenties. The results showed the profile of pregnant adolescent as primipara without marriage, eight to eleven years of study, unoccupied and cesarean delivery. Confirmed the spatial correlation between the higher incidence of GA and the highest concentration of social vulnerabilities related to education, to work, to multiparity and access to prenatal care. The impacts of the social determinants of health beckon to increasing demands intersectoral strategies in policies, projects and programs of the State.